1993
DOI: 10.1148/radiology.188.1.8511303
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular diffusion of Gd-DOTA after intravenous injection in the knee: MR imaging evaluation.

Abstract: Intraarticular concentration of gadolinium tetraazacyclododecanetetraacetic acid (DOTA) after intravenous injection and the diagnostic contribution of the subsequent arthrographic effect were assessed for meniscal lesions in the knee. Kinetics were studied in three healthy volunteers. Passage of contrast material into the synovial fluid of the joint was evaluated in 53 knees by measuring the signal intensity on T1-weighted images before, immediately after, and 1 hour after injection. Synovial fluid enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 0 publications
0
35
0
3
Order By: Relevance
“…The signal intensity of the inflamed synovial membrane on T1-weighted images increases markedly within the first minute after intravenous Gd-DTPA injection (6,7, 21,22,26,27). The signal intensity of joint effusions also increases, starting in the periphery and gradually approaching the central parts, as Gd-DTPA passes into the joint space by diffusion of fluid from synovial capillaries (5, 24,25,28). However, the rate of signal increase in effusions is much slower than in the synovial membrane (5, 25,28), and a comparison of pre-and post-aspiration volumes has indicated that misinterpretation of the effusion-synovium border is not the major source of variation when the acquisition of the MR images is completed within 10-15 minutes after Gd-DTPA injection (lo), as in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal intensity of the inflamed synovial membrane on T1-weighted images increases markedly within the first minute after intravenous Gd-DTPA injection (6,7, 21,22,26,27). The signal intensity of joint effusions also increases, starting in the periphery and gradually approaching the central parts, as Gd-DTPA passes into the joint space by diffusion of fluid from synovial capillaries (5, 24,25,28). However, the rate of signal increase in effusions is much slower than in the synovial membrane (5, 25,28), and a comparison of pre-and post-aspiration volumes has indicated that misinterpretation of the effusion-synovium border is not the major source of variation when the acquisition of the MR images is completed within 10-15 minutes after Gd-DTPA injection (lo), as in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The signal intensity of joint effusions also increases, starting in the periphery and gradually approaching the central parts, as Gd-DTPA passes into the joint space by diffusion of fluid from synovial capillaries (5, 24,25,28). However, the rate of signal increase in effusions is much slower than in the synovial membrane (5, 25,28), and a comparison of pre-and post-aspiration volumes has indicated that misinterpretation of the effusion-synovium border is not the major source of variation when the acquisition of the MR images is completed within 10-15 minutes after Gd-DTPA injection (lo), as in this study. Thus, the joint fluid that is located most peripherally may be included in the synovial membrane volume, but, at least within the initial 10 minutes after Gd-DTPA injection, other sources of variation, probably particularly coincidental variations in the outlining and partial volume artifacts, apparently are more important (10).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous injection of gadolinium can also enhance the intraarticular fluid signal. This enhancement, which can be by as much as 26096, improves the visibility of the cartilage surface (13,14). Gadolinium is also used to improve visualization of synovial inflammation (15,16).…”
Section: Technical Factors In Mrimentioning
confidence: 99%
“…Thus, the theoretical maximum interstitial concentration after an intravenous dose of 0.3 mmol/kg, or 0.21-0.23 l/kg, would be 1.3-1.4 mmol/l (14). The intraarticular gadolinium concentration measured after intravenous administration of Gd-DTPA or Gd-DOTA 0.1 mmol/kg body weight is 0.029-0.44 mmol/l (14,(52)(53)(54). These values are lower than expected based on a uniform distribution in the extracellular space because the contrast medium is rapidly excreted by the renal system and only the synovial membrane of the joint capsule can be regarded as a diffusing tissue (14,(52)(53)(54).…”
mentioning
confidence: 99%